ダイ16ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク - 酒井, 重典; サカイ, シゲノリ; 沖政, 進一; オキマサ, シンイチ; 召田, 成美; メシダ, シゲミ; 阪本, 孝広; サカモト, タカヒロ; SAKAI, Shigenori; OKIMASA, Shinichi; MESHIDA, Shigemi; SAKAMOTO, Takahiro (国立極地研究所, 1979)
P(論文) この報告は第16次南極地域観測越冬隊気象部門が,1975年2月1日から1976年1月31日まで昭和基地において行った地上および高層気象観測の結果をまとめたものである.観測方法,設備,結果の取扱い等はほぼ15次隊と同じである.16次隊の気象部門ではこの他,みずほおよび沿岸旅行に参加し,各種観測を行った.越冬期間中特記される気象現象としては,次のものがあげられる.1)1年を通して気温が低めに経過し,月平均気温が平年より2℃以上低い月が3ヵ月もあった.2)降雪量が多く,早くから本格的なドリフトが発達した.3)大型ブリザードの襲来により,16年ぶりに最大風速が更新された. This paper describes the results of meteorological observations (surface and aerological) at Syowa Station (69°00'S,39°35'E) between 1 February 1975 and 31 January 1976. The main subjects of the observations, the method, and the equipments are the same as in 1974. The data of the surface observations and the aerological observation were immediately reported to World Meteorological Center in Melbourne via Mawson Station, East Antarctica according to the WMO Regulations. The surface meteorological observations and the piball observation were also carried out en route from Syowa Station to Mizuho Station (70°42'S, 44°20'E) and in ice-free areas on the east coast of Lutzow-Holm Bay. Remarkable meteorological features of this year are as follows 1) Temperature in this season was lower than the average, especially monthly mean temperatures for April, July and August were lower than normal year by 2℃ or more. 2) Amount of snow accumulation was larger than that of normal year. 3) Maximum wind speed brought by the severe blizzard at the end of May recorded the highest value ever since Syowa Station was opened. departmental bulletin paper